Textbook journalism? Objectivity, education and the professionalization of sports reporting. (October 2020) - Weedon, Gavin; Wilson, Brian
In this article, we present an analysis of recent handbooks, field guides and other educative texts on sports journalism. Authored mostly by current and former journalists turned university educators, these books signal the professionalization of sports journalism amid changes and challenges to news media industries. In offering guidance on best practice sports reporting, they are also situated in tension with the long-standing denigration of sports journalism as the trivial back-page filler that props up more serious, substantive content. Through a thematic analysis of the textbooks' contents and the epistemic, economic and educative context of their collective emergence, we address the following question in what follows: How do these textbooks advise would-be sports journalists to respond to 'serious' social, ethical and political matters? In doing so, we detail how established categories of objectivity and ethics are the primary points of recourse through which these books advise on reporting about the many social issues in which sport is implicated. In turn, we reflect on the virtues of – and the tensions and contradictions surrounding – these advocations. By way of conclusion, we contend that professionalization represents an opportunity for collaborations between sport media scholars and current and former journalists – in their shared roles as educators – in the pursuit of 'excellent' sports reporting. The notion of 'strong objectivity' is our conceptual guide for how such collaborations might be fostered.